2018
DOI: 10.3390/molecules23071515
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Ruthenium Complexes Covalently Linked to Nucleic Acid Derivatives

Abstract: Oligonucleotides are biopolymers that can be easily modified at various locations. Thereby, the attachment of metal complexes to nucleic acid derivatives has emerged as a common pathway to improve the understanding of biological processes or to steer oligonucleotides towards novel applications such as electron transfer or the construction of nanomaterials. Among the different metal complexes coupled to oligonucleotides, ruthenium complexes, have been extensively studied due to their remarkable properties. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 172 publications
(198 reference statements)
0
18
0
Order By: Relevance
“…Other cytotoxic activities from NAMI-A and KP1019 may be attributed to their interactions with DNA nucleobases generally to the N7 site of guanine. 17,24 It is worth mentioning that interaction of ruthenium compounds with nucleic acid and derivatives generates compounds with chemical and photophysical properties with important applications in nanotechnologies, medical diagnosis and therapies, and have recently been reviewed by Flamme et al 69 Since our results suggested that both NAMI-A, KP1019 and their hydrolyzed products are very prone to be reduced, we evaluated the affinity of the NAMI-A and KP1019 for different intracellular components, though the calculation of the thermodynamics of the interaction of the reduced and mono-hydrated forms of NAMI-A and KP1019 with different S-donors (GSH and Cys) and N-donors (GN3 and GN7 sites) ligands.…”
Section: S2 (Si Section)mentioning
confidence: 99%
“…Other cytotoxic activities from NAMI-A and KP1019 may be attributed to their interactions with DNA nucleobases generally to the N7 site of guanine. 17,24 It is worth mentioning that interaction of ruthenium compounds with nucleic acid and derivatives generates compounds with chemical and photophysical properties with important applications in nanotechnologies, medical diagnosis and therapies, and have recently been reviewed by Flamme et al 69 Since our results suggested that both NAMI-A, KP1019 and their hydrolyzed products are very prone to be reduced, we evaluated the affinity of the NAMI-A and KP1019 for different intracellular components, though the calculation of the thermodynamics of the interaction of the reduced and mono-hydrated forms of NAMI-A and KP1019 with different S-donors (GSH and Cys) and N-donors (GN3 and GN7 sites) ligands.…”
Section: S2 (Si Section)mentioning
confidence: 99%
“…Oligonucleotides functionalized with transition metal ions are studied intensively for potential applications in DNA nanotechnology 14 as well as diagnostics and chemotherapy. 58 Such structures are typically obtained through coordination of the desired metal ion to a high-affinity ligand within the oligonucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…Although not reviewed in detail in this manuscript, biomolecules, such as amino acids, vitamins, and carbohydrates, are among the most common and broadly studied delivering agents of anticancer drugs into tumors [ 11 ]. There are numerous reports of bioconjugates containing ruthenium and gold complexes for targeted anticancer applications that have been reported and discussed elsewhere [ 98 , 99 , 100 , 101 , 102 ]. Herein, we selected a couple of examples for illustrative purposes (see Section 5.2 ).…”
Section: Other Emerging Targetsmentioning
confidence: 99%